Coupling effects of glass fiber treatment and matrix modification on the interfacial microstructures and the enhanced mechanical properties of glass fiber/polypropylene composites. (15th February 2017) - Luo, Guojun; Li, Wenze; Liang, Wenbin; Liu, Guogang; Ma, Yi; Niu, Yanhua; Li, Guangxian
Abstract: High performance polypropylene/glass fiber (PP/GF) composites were prepared by treating GF with a film former (GFf) containing a certain ratio of maleic anhydride grafted polypropylene (MPP) and a kind of β-nucleating agent (TMB-5) via impregnation method, and meanwhile introducing different amount of MPP in the matrix. The coupling effects of GF treatment and the matrix modification on the mechanical properties and interfacial microstructures were investigated in detail. It is found that the film former can efficiently facilitate both the interfacial adhesion and β-transcrystallinity with the aid of appropriate MPP in the matrix. Addition of small amount of MPP (2 wt%) to the matrix in GFf system could significantly improve the mechanical properties with ca. 100% and 178% enhancements in tensile and impact strength, respectively, compared to the commercial GF reinforced PP (PP/GFc). With further increase of MPP content, the tensile strength of the composite increases slightly, accompanied by deterioration of the impact strength. The dramatically improved mechanical properties can be attributed to the simultaneously enhanced interfacial adhesion and β-form transcrystallinity through the coupling effects of nucleating agent locked by MPP on the surface of GFf and those MPP in both the film former and matrix. A schematic mechanism of interfacial microstructure formation is depicted, in which the diffusivity of MPP and PP, the nucleating agent and the molecular interactions are considered as key factors influencing the formation of β-transcrystallinity and interfacial adhesion.